Using high-throughput approaches to unveil sporulation and germination mechanisms in Clostridium sporogenes - Mesquita Rodrigues, Raquel (2020)
Intravenously injected clostridial spores infiltrate and selectively germinate in the hypoxic regions of solid tumours. The exquisite selectivity of this natural phenomenon is being exploited to bring about tumour destruction by engineering the delivered clostridia to enzymatically convert a subsequently injected circulatory prodrug into a highly cytotoxic species. This approach is termed ‘Clostridial-Directed Enzyme Prodrug Therapy’ (CDEPT), and its leading chassis is Clostridium sporogenes, a non-pathogenic member of the genus and a prolific producer of spores. Despite its central role in CDEPT, spore formation and germination in C. sporogenes remain relatively poorly understood. A better understanding would allow the implementation of further refinements to CDEPT, in particular the creation of a conditionally sporulating strain. Accordingly, to gain greater insight into these two developmental processes, TraDIS (Transposon Directed Insertion-site Sequencing) and RNA-Seq were undertaken. The former to identify those genes essential to sporulation and germination, the latter to identify the regulons of the main sporulation sigma factors, σF, σE, σG and σK. The implementation of TraDIS initially required improvements to the frequency of DNA transfer into C. sporogenes NCIMB 10696 through circumvention of the barriers posed by two native restriction modification systems. Conjugation efficiencies were increased more than 10-fold using E. coli sExpress as the conjugative donor. The TraDIS library made contained 118,894 unique insertion sites, equivalent to one transposon insertion every 35 bp. A total of 471 genes were identified as essential for the survival of the organism, corresponding to almost 13% of the annotated genes. Some 183 and 142 genes were considered essential for sporulation and germination, respectively. Some of these genes identified as essential were further characterised, namely sigF, sigE, sigG, sigK, spoIIAA, spoIIE, spoIIR, gerKA4, CLSPO_c22010 and CLSPO_c33910. Overall, this work shed some light on sporulation and germination mechanisms in C. sporogenes and highlighted some similarities and differences relative to other spore formers. Furthermore, the genes identified using TraDIS as essential for sporulation can be explored in the future regarding their use in the generation of a conditionally sporulating strain.